KAJIAN YURIDIS PRILAKU KORUPSI PEJABAT PUBLIC DI ERA OTONOMI DAERAH DITINJAU DARI PERSPEKTIF PEMERINTAHAN YANG BAIK - MZ, H. ISMAIL (GANEC SWARA, 2019)
Corruption shares parasites which caused this nation to collapse. The regime has changed from the revision of old orders, new orders, and reform orders, none of which have succeeded in eradicating corruption. Even lately the practice has been very chronic and has spread throughout the components of this nation. We are well aware of how corruption is a serious problem, like a disease that has entered the acute stage category and has taken root in the lives of our society. At the same time corruption has reduced the image of the government and officials, both at the central and regional levels. Even bureaucracy loses trust, clean, honest and transparent governance is very difficult to achieve.     One of the things that is often addressed in the context of efforts to eradicate corruption in the Central and Regional Centers is how to create Good Governance. The concept of good governance is at least a control of the state apparatus in terms of the rules of the game and procedures for living a nation, state and community, so that the effort to create a clean government and uphold the rule of law can work well. Speaking of good governance must be in line with bureaucratic reform. With the implementation of bureaucratic reforms well, it is hoped that simultaneous development will occur between bureaucratic reform and democracy. Because, until now these two things, between bureaucratic reform and democracy still face severe challenges, which ultimately will have an impact on the increasingly difficult to eradicate corruption in Indonesia.